Postpartum sex taboos and child growth in Tanzania: Implications for child care - Zaina Mchome; Ajay Bailey; Flora Kessy; Shrinivas Darak; Hinke Haisma (Wiley, 2020)
Abstract The social context and cultural meaning systems shape caregivers' perceptions about child growth and inform their attention to episodes of poor growth. Thus, understanding community members' beliefs about the aetiology of poor child growth is important for effective responses to child malnutrition. We present an analysis of caregivers' narratives on the risks surrounding child growth during postpartum period and highlight how the meanings attached to these risks shape child care practices. We collected data using 19 focus group discussions, 30 in‐depth interviews and five key informant interviews with caregivers of under‐five children in south‐eastern Tanzania. Parental non‐adherence to postpartum sexual abstinence norms was a dominant cultural explanation for poor growth and development in a child, including different forms of malnutrition. In case sexual abstinence is not maintained or when a mother conceives while still lactating, caregivers would wean their infants abruptly and completely to prevent poor growth. Mothers whose babies were growing poorly were often stigmatized for breaking sex taboos by the community and by health care workers. The stigma that mothers face reduced their self‐esteem and deterred them from taking their children to the child health clinics. Traditional rather than biomedical care was often sought to remedy growth problems in children, particularly when violation of sexual abstinence was suspected. When designing culturally sensitive interventions aimed at promoting healthy child growth and effective breastfeeding in the community, it is important to recognize and address people's existing misconceptions about early resumption of sexual intercourse and a new pregnancy during lactation period.